Coating-dependent induction of cytotoxicity and genotoxicity of iron oxide nanoparticles. Issue 1 (May 2015) - Magdolenova, Zuzana; Drlickova, Martina; Henjum, Kristi; Rundén-Pran, Elise; Tulinska, Jana; Bilanicova, Dagmar; Pojana, Giulio; Kazimirova, Alena; Barancokova, Magdalena; Kuricova, Miroslava; Liskova, Aurelia; Staruchova, Marta; et al.
Abstract Surface coatings of nanoparticles (NPs) are known to influence advantageous features of NPs as well as potential toxicity. Iron oxide (Fe3O4) NPs are applied for both medical diagnostics and targeted drug delivery. We investigated the potential cytotoxicity and genotoxicity of uncoated iron oxide (U-Fe3O4) NPs in comparison with oleate-coated iron oxide (OC-Fe3O4) NPs. Testing was performed in vitro in human lymphoblastoid TK6 cells and in primary human blood cells. For cytotoxicity testing, relative growth activity, trypan blue exclusion, 3H-thymidine incorporation and cytokinesis-block proliferation index were assessed. Genotoxicity was evaluated by the alkaline comet assay for detection of strand breaks and oxidized purines. Particle characterization was performed in the culture medium. Cellular uptake, morphology and pathology were evaluated by electron microscopy. U-Fe3O4 NPs were found not to be cytotoxic (considering interference of NPs with proliferation test) or genotoxic under our experimental conditions. In contrast, OC-Fe3O4 NPs were cytotoxic in a dose-dependent manner, and also induced DNA damage, indicating genotoxic potential. Intrinsic properties of sodium oleate were excluded as a cause of the toxic effect. Electron microscopy data were consistent with the cytotoxicity results. Coating clearly changed the behaviour and cellular uptake of the NPs, inducing pathological morphological changes in the cells.